An experimental assessment of rotor superconducting stack demagnetization in a liquid nitrogen environment. (8th July 2019) - Smara, Anis; Mineev, Nikolay; Climente-Alarcon, Vicente; Patel, Anup; Baskys, Algirdas; Glowacki, Bartek A; Reis, Thomas
Abstract: Stacks of high-temperature superconducting tape have proved to trap in laboratory conditions levels of magnetic flux density one order of magnitude above actual state-of-the-art permanent magnets. Their simple manufacturing, high mechanical properties and intrinsic resistance to sudden quench greatly facilitate their utilization in industrial applications, amongst them, as a source of magnetic flux density in the rotor of electrical machines. For this to happen, the currents induced in the superconducting layers of the stack must not be disturbed during operation. This work studies in experimental conditions the demagnetization of a stack rotating in the airgap of an electrical motor under slot and winding-induced cross-field components, whose values are estimated via conventional 2D finite element analysis. The results are congruent with previous laboratory studies and show small long-term demagnetization rates that may allow operation for time spans longer than initially established.